PENERAPAN MODEL PEMBELAJARAN PJBL DALAM MENINGKATKAN KREATIVITAS SISWA MELALUI KEGIATAN MARKET DAY - Sormin, Yeyen; Ananthia, Winti; Furnamasari, Yayang Furi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the implementation of a learning model that is still teacher-centered and the low creativity of fourth grade students of SD Negeri Pantai Hurip 01. The objectives of this study are 1) To describe the implementation of the Project Based Learning (PjBL) learning model through the P5 Market Day activity. 2) To describe students' responses to the P5 Market Day activity. 3) To describe the supporting and inhibiting factors in the implementation of the Project Based Learning model. This study applies a qualitative approach with a qualitative descriptive analysis research type. Data collection techniques applied in this study are interviews, questionnaires, and document studies. The data analysis technique used is Miles and Huberman's qualitative data analysis which includes data collection, data reduction, data presentation, and conclusions or verification. The results of this study, namely 1) The application of the PjBL learning model has been applied with a good category according to the PjBL steps, 2) The response given by students to the application of the PjBL learning model through Market Day activities is very positive. 3) Supporting and inhibiting factors that are seen in increasing the creativity of grade IV students.